Analyzing the Use of Snowball Throwing Model to Enhance Comprehension of Linear Functions: A Qualitative Study - Abiyoso, Nur Ahmad; Faradiba, Surya Sari; Fuady, Anies (Department of Mathematics Education, Faculty of Teacher Training and Education, Wisnuwardhana University of Malang, 2025)
This study aims to explore the teaching and learning process of linear functions through the implementation of the Snowball Throwing learning model. A qualitative approach was employed, with data collected via observations, in-depth interviews, and documentation of the learning activities. The findings reveal that the Snowball Throwing model’s syntax—including the delivery of material, group formation, group leader explanations, question writing and throwing, as well as group discussion and evaluation—creates an active and collaborative learning environment. This process encourages students to develop key indicators of mathematical conceptual understanding: the ability to restate the concept of linear functions in their own words, classify objects according to the concept’s characteristics, and provide accurate examples and non-examples. Moreover, students demonstrate the ability to represent the concept in various mathematical forms, such as graphs and algebraic expressions, and apply the concept effectively in solving contextual problems. The interactive question-and-answer sessions and group discussions prove effective in strengthening conceptual understanding and clarifying misconceptions. This study recommends the use of the Snowball Throwing model as a participatory teaching strategy to enhance student engagement and improve the quality of mathematical conceptual understanding, particularly in the topic of linear functions.